Influencia de la relación ácido carmínico / antocianinas en celdas solares fotovoltaicas para la obtención de energía eléctrica - Armas Ruíz, Diana Azucena (2017)
In the present research the influence of the mixture of two natural dyes such as carminic acid and anthocyanins was studied in obtaining electric energy through solar cells sensitized with dyes during 60 days of exposure to solar radiation. Different concentrations of anthocyanins (300ppm, 600ppm and 1300ppm) and of carminic acid (500ppm, 10000ppm and 25000ppm) were prepared to determine the influence of the concentration of a dye in the generation of energy. The results showed that mixtures with: 300ppm of anthocyanins and 500ppm of carminic acid as well as 1300ppm of anthocyanins and 10000ppm of carminic acid have a synergistic effect on the increase of energy generation in 26.4% and 29.4% in voltage, and 33.3% and 20.8 % in amperage, respectively. Likewise, only in the case of carminic acid, the generation of energy depends on the concentration of the dye